1989
DOI: 10.1111/j.1600-051x.1989.tb01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal condition and microbiology of healthy and diseased periodontal pockets in type 1 diabetes mellitus patients

Abstract: On the basis of glycosylated hemoglobin (HbA1c) values, 22 type 1 (insulin-dependent) diabetic adults were grouped into patients with near normal (HbA1c less than or equal to 7.7%) and poor (HbA1c greater than or equal to 9.9%) metabolic control. A total of 44 subgingival sites were examined for Actinobacillus actinomycetemcomitans, black-pigmented Bacteroides species and Capnocytophaga species. No significant difference could be demonstrated between patients in the 2 test groups with regard to periodontal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 39 publications
2
64
0
6
Order By: Relevance
“…37 In several studies, rapid periodontal breakdown in adults with poorly controlled diabetes as a result of high blood glucose levels was reported. 37 -39 However, Sastrowijoto et al 40 found that although metabolic control was improved by conventional insulin treatment in IDDM patients, no improvement was seen in the clinical periodontal condition, with the exception of a decrease in gingival redness.…”
Section: R Orbak a Tezel V çAnakçi Et Al Smoking And Niddm In Perimentioning
confidence: 99%
“…37 In several studies, rapid periodontal breakdown in adults with poorly controlled diabetes as a result of high blood glucose levels was reported. 37 -39 However, Sastrowijoto et al 40 found that although metabolic control was improved by conventional insulin treatment in IDDM patients, no improvement was seen in the clinical periodontal condition, with the exception of a decrease in gingival redness.…”
Section: R Orbak a Tezel V çAnakçi Et Al Smoking And Niddm In Perimentioning
confidence: 99%
“…El análisis del PCR de nuestra investigación muestran una alta presencia de Treponema denticola y Tannerella forsythia, seguida de Porphyromonas gingivalis y Aggregatibacter actinomycetemcomitans (Tabla 5). Estos resultados son similares a los obtenidos por Makiura y cols (29) , sin embargo contrastan con otros estudios que detectaron mayor presencia de Porphyromonas gingivalis que de Treponema denticola y Aggregatibacter actinomycetemcomitans (30)(31)(32)(33) . Al analizar la presencia de las bacterias estudiadas según severidad de la periodontitis, Treponema denticola, Tannerella forsythia y Porphyromonas gingivalis se presentaron en mayor porcentaje en los sujetos con periodontitis moderada y severa.…”
Section: Discussionunclassified
“…Sastrowijotosh et al (1989) showed that Capnocytophaga species were isolated at very low levels, in both the diseased and healthy periodontal pockets (8). Thus the role of Capnocytophaga species in the pathogenesis of infectious periodontal disease in patients with type I diabetes may be over estimated.…”
Section: Alterations In Subgingival Microbiota and Gingival Creviculamentioning
confidence: 99%